2011
DOI: 10.1007/s00345-011-0749-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific PCA3 score reference values for diagnosis of prostate cancer

Abstract: PCA3 score increases with age, independent of PCa presence. Age-specific PCA3 score reference values are superior to PSA, continuous PCA3 score, and PCA3-35 in predicting initial pBx outcome. Therefore, an age-adjusted PCA3 score should be used for interpretation of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…We also found no significant correlations between urine PCA3 or TMPSS2:ERG scores with IPSS score, PSA doubling time, or the use of statins, diabetes medications, 5 α-reductase inhibitors, or NSAIDs (data not shown). TMPRSS2:ERG score was not correlated with age, but PCA3 levels were positively correlated with advancing age ( P < 0.0001), as has been observed by others (38). …”
Section: Resultssupporting
confidence: 82%
“…We also found no significant correlations between urine PCA3 or TMPSS2:ERG scores with IPSS score, PSA doubling time, or the use of statins, diabetes medications, 5 α-reductase inhibitors, or NSAIDs (data not shown). TMPRSS2:ERG score was not correlated with age, but PCA3 levels were positively correlated with advancing age ( P < 0.0001), as has been observed by others (38). …”
Section: Resultssupporting
confidence: 82%
“…Furthermore, these relationships are generally explored in at-risk populations referred for prostate biopsy, in which the presence or absence of cancer strongly drives observations, potentially confounding the true relationship between biomarkers and noncancer factors. Klatte et al [25] previously assessed the association of PCA3 with age among 205 men referred for 14-core biopsy because of PSA >3.0 ng/ml or suspicious DRE. On biopsy, 76 men (37%) had cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Group comparison analysis was performed using nonparametric Wilcoxon Kruskal-Wallis tests with post hoc analyses idem for the categorized variables. A multivariate logistic regression model with age and Gleason score as confounding variables [4,10] was constructed. In the group of patients with negative biopsy results, the PCA3 score was compared to the inflammation scores.…”
Section: Methodsmentioning
confidence: 99%
“…Hennenlotter For example, prostate inflammation may alter the test quality or accuracy as the samples used consist of expressed urine following standardized digital rectal manipulation. Previous analyses have shown that patient age affects the result [4].…”
Section: Introductionmentioning
confidence: 97%